Proceedings of the 22nd ACM Conference on Hypertext and Hypermedia 2011
DOI: 10.1145/1995966.1995992
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the structure and evolution of discussion cascades

Abstract: We analyze the structure and evolution of discussion cascades in four popular websites: Slashdot, Barrapunto, Meneame and Wikipedia. Despite the big heterogeneities between these sites, a preferential attachment (PA) model with bias to the root can capture the temporal evolution of the observed trees and many of their statistical properties, namely, probability distributions of the branching factors (degrees), subtree sizes and certain correlations. The parameters of the model are learned efficiently using a n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 26 publications
(39 reference statements)
3
64
0
Order By: Relevance
“…This discrete-time model extends previous generative models for discussion threads [83,92]. Besides popularity and novelty features (parameterized with α and τ respectively), it considers an additional feature (a root bias) that makes explicit the difference between the process of writing to the post (with id 0) node and to a descendant (user comment).…”
Section: Gómez Et Al [85]mentioning
confidence: 99%
See 1 more Smart Citation
“…This discrete-time model extends previous generative models for discussion threads [83,92]. Besides popularity and novelty features (parameterized with α and τ respectively), it considers an additional feature (a root bias) that makes explicit the difference between the process of writing to the post (with id 0) node and to a descendant (user comment).…”
Section: Gómez Et Al [85]mentioning
confidence: 99%
“…While the threads sizes analyzed in some studies followed heavy-tailed distributions [83,92], other previous studies reported distributions with a light tail [93,94]. Wang et al [84] first observes that the waiting time between two consecutive comments from a user follows a upper truncated Pareto distribution.…”
Section: Wang Et Al [84]mentioning
confidence: 99%
“…Any account of technical communication has to consider this social dimension (cf. Zerubavel, 2003) -otherwise it fails to clarify the peculiarities of technological enhancements of, say, collaborative writing as currently provided by wiki-based systems (Leuf and Cunningham, 2001;Stegbauer, 2009 (Wattenberg, Viégas, and Hollenbach, 2007;Laniado, Tasso, Volkovich, and Kaltenbrunner, 2011;Gómez, Kappen, and Kaltenbrunner, 2011) (Mehler and Sutter, 2008)) to collaborative writing and edit wars (where articles are authored by many authors in the role of content providers, removers or defenders (Brandes, Kenis, Lerner, and Raaij, 2009) (Sager, 1997). They also allow for suspending the time-space continuity of faceto-face communication (Zerubavel, 2003) in terms of multilogues.…”
Section: Social Complexity In the Range Of Monades Dyads Triads Anmentioning
confidence: 99%
“…As an early example, Granovetter suggested that "the number or proportion of others who must make one decision before a given actor does so" is a fundamental personal trait driving the contagion [2]. It is straightforward to see that this type of dynamics is sensitive to network structure [5][6][7][8][9][10]. This paper investigates what happens if a threshold, such as the one Granovetter mentions, depends on the how influential a node is.…”
Section: Introductionmentioning
confidence: 99%
“…Since Granovetter, there has been many papers investigating the relation between the network structure and opinion dynamics [5][6][7][8][9][10]. Perhaps the most influential paper was Watts's study of threshold models as an explanation of cascades or fads [5].…”
Section: Introductionmentioning
confidence: 99%